Paraconsistent Annotated Logic Algorithms Applied in Management and Control of Communication Network Routes - Da Silva Filho, João Inácio; Abe, Jair Minoro; Marreiro, Alessandro de Lima; Martinez, Angel Antonio Gonzalez; Torres, Cláudio Rodrigo; Rocco, Alexandre; Côrtes, Hyghor Miranda; Mario, Mauricio Conceição; Pacheco, Marcos Tadeu Tavares; Garcia, Dorotéa Vilanova; Blos, Maurício Fontoura (Sensors (Basel, Switzerland), 2021)
This paper presents a computational method based on non-classical logic dedicated to routing management and information stream control in communication networks. Paraconsistent logic (PL) was used to create an algorithmic structure whose main property is to accept contradiction. Moreover, a computational structure, the denominated paraconsistent data analyzer (PDAPAL2v), was constructed to perform routing management in communication networks. Direct comparisons of PDAPAL2v with a classical logic system that simulates routing conditions were made in the laboratory. In the conventional system, the paraconsistent algorithms were considered as binary logic gates, and in the tests, the same adjustment limits of PDAPAL2v were applied. Using a database with controlled insertion of noise, we obtained an efficacy of 97% in the detection of deteriorated packets with PDAPAL2v and 72% with the conventional simulation system. Functional tests were carried out, showing that PDAPAL2v is able to assess the conditions and degradation of links and perform the analysis and correlation of various inputs and variables, even if the signals have contradictory values. From practical tests in the laboratory, the proposed method represents a new way of managing and controlling communication network routes with good performance.